The Role of Family Support in Gay and Lesbian Individuals' Experiences of Sexual Identity-Based Discrimination, Harassment, and Violence: An Empirical Test of Norm-Centered Stigma Theory. Issue 3 (4th March 2023) - Worthen, Meredith G. F.; Jones, Melissa S.
ABSTRACT: Many gay and lesbian individuals struggle with family support throughout their life course. In addition, due to their differences in social power and violations of heteronormativity, gay men and lesbian women have unique experiences with family distress. Such difficulties can be related to an increased risk for sexual identity-based discrimination, harassment, and violence (DHV) among gay and lesbian individuals, yet few studies have examined these relationships. The current study utilizes data stratified by US Census categories (age, gender, race/ethnicity, and census region) collected from online panelists (N = 2159; n = 750 hetero cis men, n = 749 hetero cis women, gay cis men = 330, lesbian cis women = 330) to explore Norm-Centered Stigma Theory (NCST) and the relationships between gay/lesbian identity and sexual identity-based DHV. Specifically, social power axes (gender identities), family support, and interactions among these are investigated as they moderate the relationships between violations of heteronormativity (gay/lesbian identity) and stigmatizing experiences associated with such norm violations (sexual identity-based DHV). Results indicate that gay/lesbian identity increases the likelihood of experiencing sexual identity-based DHV; however, family support among lesbian women and gay men decreases the odds of experiencing sexual identity-based DHV. Overall, results lend support to the use of NCST in intersectional explorations to better understand gay and lesbian experiences.